Changing Personal Values through Value-Manipulation Tasks: A Systematic Literature Review Based on Schwartz's Theory of Basic Human Values - Claudia Russo; Francesca Danioni; Ioana Zagrean; Daniela Barni (MDPI AG, 2022)
According to the Theory of Basic Human Values, values are relatively stable, but not immutable, abstract goals which strongly influence peoples' lives. Since their relative stability, psychosocial research is attempting to understand the extent to which it is possible to induce a voluntary change in people's personal values. The main aim of this study was to systematically review the existing literature on experiments to induce a value change, also highlighting the theoretical perspectives used to develop the experimental tasks. We conducted a literature search of five databases (SCOPUS, ProQuest, PsycINFO, PubMed, and Web of Science). After the screening and the eligibility phase, we included a total of 14 articles (25 experiments). Most of these studies involved university students and adopted a pre-and post-test design, using different manipulation tasks. The results highlighted the possibility of inducing a voluntary value change, assessed in terms of mean levels and/or rank order. These findings provide new insights regarding the stability of values in the light of the Theory of Basic Human Values. The practical implications and future research directions are discussed.